Nutrition and mental health: A review of current knowledge about the impact of diet on mental health - Grajek, Mateusz; Krupa-Kotara, Karolina; Białek-Dratwa, Agnieszka; Sobczyk, Karolina; Grot, Martina; Kowalski, Oskar; Staśkiewicz, Wiktoria (Frontiers in Nutrition, 2022)
Applied psychopharmacotherapy and psychotherapy do not always bring the expected results in the treating of mental disorders. As a result, other interventions are receiving increasing atten-tion. In recent years, there has been a surge in research on the effects of nutrition on mental status, which may be an important aspect of the prevention of many mental disorders and, at the same time, may lead to a reduction in the proportion of people with mental disorders. The aim of this review is to answer whether and to what extent lifestyle and related nutrition affect mental health and whether there is scientific evidence supporting a link between diet and mental health. A review of the scientific evidence was conducted based on the available literature by typing in phrases related to nutrition and mental health using the methodological tool of the PubMed da-tabase. The literature search yielded 3473 records, from which 356 sources directly related to the topic of the study were selected, and then those with the highest scientific value were selected according to bibliometric impact factors. In the context of current changes, urbanization, global-ization, including the food industry, and changes in people's lifestyles and eating habits, the correlations between these phenomena and their impact on mental state become important. Knowledge of these correlations creates potential opportunities to implement new effective die-tary, pharmacological, therapeutic, and above all preventive interventions. The highest thera-peutic potential is seen in the rational diet, physical activity, use of psychobiotics, consumption of antioxidants. Research also shows that there are nutritional interventions that have psychopro-tective potential.